O kategorii płci i rodzaju w polszczyźnie - Nowosad-Bakalarczyk, Marta (Vilnius University Open Series, 2020)
Artykuł dotyczy wybranych aspektów relacji płci i języka w polszczyźnie. Punkt wyjścia rozważań stanowi pojęcie płci – ukształtowane na bazie istniejących (i dostrzeganych) różnic biologicznych w świecie ludzi i zwierząt (ang. sex), ugruntowane (reprodukowane) kulturowo (ang. gender). Punktem dojścia zaś jest zdanie sprawy z tego, jak to pojęcie jest kodowane w języku. W artykule zaprezentowano różne typy eksponentów męskości i żeńskości: leksykalne, morfologiczne (fleksyjne i słowotwórcze), tekstowe i kontekstowe. Ustalono, że w konkretnych wypowiedziach mamy do czynienia z ich różnymi kombinacjami. O wyborze sposobu eksponowania płci decyduje splot wielu czynników: językowych, pragmatycznych, a także psychologiczno-społecznych. The most effective (unequivocal) way to express grammatical gender is to use appropriate lexical means, i.e. primary words for sex/gender (kobieta – mężczyzna) [man and woman] and given names (Adam – Ewa). Morphological and syntactical markers are effective only in the case of expressing the feminine gender (except few instances), e.g. Lekar-ka czekał-a w gabinecie; Spotkał-a-m Nowak-ową [The <female> doctor waited in the doctor’s office; I < female speaker>, have met Mrs Nowak]. Morphological and syntactical markers of the masculine gender are ambiguous, e.g. Udało mi się zapisać do lekarza w nieodległym terminie, Lekarze składają przysięgę Hipokratesa [I was able to make an appointment with a doctor <masculine grammatical gender, sex/gender unspecified> at a near future date; Doctors <unmarked/masculine grammatical gender, sex/gender unspecified> take the Hippocratic Oath], and, as such, have to be supported by lexical, contextual, or constitutive hints indicating the biological sex of the referent. For example: Udało mi się zapisać do znajomego lekarza w nieodległym terminie, Lekarze i lekarki składają przysięgę Hipokratesa [I was able to make an appointment with a doctor whom I know at a near future date, Doctors <unmarked/masculine gender> and female doctors take the Hippocratic Oath]. The author concludes that one has to include not only the strictly linguistic categories in the way of expressing the biological sex in language, but also pragmatic categories such as the type of the communicative situation (official or unofficial), the intention of the utterance (e.g. hiding or emphasising the biological sex, the importance of such a piece of information in a given act of communication). Psycho-social factors are also important. This includes the acceptance (or lack of it) of a certain way of expressing the gender (e.g. the usage of feminine word formations such as prezeska [<female> director] or socjolożka [<female> sociologist]).